Counterfeit? I don’t mind: The perspective of fashion consciousness, subjective norm and hedonic shopping motivation - Yulianti, Ni Made Dhian Rani; Saputra, A. A. Gd. Deni Windu (International research journal of management, IT and social sciences, 2021)
The purpose of this study was to determine how the influence of Fashion Consciousness, Subjective Norm, and Hedonic Shopping Motivation on Purchase Intention of counterfeit fashion products. This study used a quantitative approach that targets youth consumers in Denpasar City. Data was collected through an online questionnaire using a google form involving 100 respondents. The data were analyzed using SPSS software version 26.0. This research provides evidence that purchase intention is influenced by fashion consciousness and hedonic shopping motivation, while the subjective norm has no significant effect on the purchase intention of counterfeit fashion products. This research has implications for fashion product entrepreneurs, both original and counterfeit products, regarding the internal factors of consumers that influence purchase intentions on fashion products, especially counterfeit fashion products.